Views of mathematics and vocational teachers in upper secondary schools about which forces impact assessment practices and the use of information technology - Eiríksdóttir, Elsa; Jóhannesson, Ingólfur Ásgeir (Menntavísindasvið Háskóla Íslands, 2016)
The aim of the study was to understand how teachers in Icelandic upper secondary schools describe forces influencing changes in their teaching practices. Specifically, what they identify as the impetus for changes and how they frame them. The past decade has seen a series of changes to the upper secondary school level in Iceland, through amendments to legislation in 2008, the adoption of a new curriculum in 2011, and a recent initiative to shorten the duration of the upper secondary school from four to three years. These and other developments, such as the enrollment of an ever larger percentage of cohorts and the increasing ubiquity of information technology, are likely to affect the work of teachers. However, little is known as to how teachers view and frame the modifications they make to their teaching practices.We analyzed interviews with six mathematics and six vocational teachers from eight different upper secondary schools, conducted between late 2013 and late 2014. We composed an analytical device consisting of two spectra: On the Y-spectrum we placed reasons for change; with changes viewed as top-down at one end (e.g., educational authorities, school policy) and changes seen as initiated by the teachers themselves on the other. The X-spectrum reflects whether the teachers frame the changes as peripheral (e.g., adjustments made to solve practical issues) or structural (e.g., reflecting pedagogical beliefs or values), corresponding roughly to the processes described by Piaget (1954) and Kolb (e.g., Kolb, Boyatzis, & Mainemelis, 2000) as assimilation and accommodation. The analysis revealed that the changes referred to by the teachers fell into two main categories: assessment and technology. Overall, the analysis revealed that the immediate school environment, students, and school policy are perceived as the main motivators for changes in assessment practices and the use of information technology. The results also indicate interplay between school policy and teacher initiative, with one seemingly ...